A novel waterborne polyurethane coating modified by highly dispersed nano‐boron carbide particles. Issue 15 (7th November 2020) - Sun, Yingchun; Wu, Yan; Yang, Feng; Wu, Xinyu; Ding, Guanfen
Abstract: In this study, waterborne polyurethane (WPU) coatings were modified by adding various compositions of nano‐boron carbide (nano‐B4 C) particles. In order to achieve proper dispersion of nano‐B4 C in WPU and increasing chemical interactions between them, the nano‐B4 C particles were treated with polyethylene glycol (PEG) or polypropylene glycol (PPG). The modified surface and microstructure of nano‐B4 C were characterized by Fourier transform infrared, scanning electron microscopy and transmission electron microscopy. The deposition experiment was designed to evaluate the dispersion effect of nano‐B4 C in PEG or PPG aqueous solution. The physical performance of nano‐B4 C modified WPU coatings was measured following the national standards of paints and vanishes. The results revealed that the PEG6000 not only enhanced the interaction between nano‐B4 C and WPU but also exhibited a remarkable ability to improve the physical performance of WPU coating. The coating with 15 wt% of nano‐B4 C addition exhibited the best performance in terms of abrasion and hardness, which could be attributed to the best uniform dispersion of nano‐B4 C particles in PEG6000 aqueous solution. Abstract :